RANCANG BANGUN VENTURI SCRUBBER TERHADAP PENURUNAN EMISI JELAGA - Prabowo, Dian; Syaiful, Syaiful; Jamari, Jamari (Infotekmesin, 2019)
The industrial world and vehicles that currently exist make the pollution level increase. Often we see thick smoke rising out of the factory chimney, the thick smoke is a waste of gas released by the environmental factory. The scrubber system is a collection of various air pollution control devices that can be used for particles and / or gases from industrial output gas streams. The term scrubber is also used to describe a system that injects or enters a dry active ingredient or liquid into a dirty gas stream to clean acid gas. The design of the venturi scrubber aims to design a venturi scrubber to reduce soot emissions on direct injection diesel engines, get a standard venturi scrubber design and reduce soot levels. This design begins with determining the alternative design, determining the venturi dimensions and the material that will be used to build the venturi scrubber. The result of this step is a working drawing that is ready to be realized through machining. Next is to make the components based on the design results in the previous step. These components are then assembled into a tool. The final step is to do the venturi design test according to the venturi type standard and the size requirements that are in the ISO 5167-4 standard. Making a venturi scrubber design program using Delphi-7 software with pressure drop data, liquid to gas ratio, diameter ratio, pipe diameter, throat diameter, renold number and type of flow that occurs and design using Solidworks 2010.